PERTIMBANGAN HAKIM DALAM PENDEWASAAN ORANG (STUDI DI PENGADILAN AGAMA BAWEAN PADA CALON MEMPELAI PEREMPUAN) - Gunawan Marsudi (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2019)
This paper discusses the implementation of Maturity (for brides-to-be) in the Bawean Religious Court. With the number of marriages occurring in Indonesia, the government issued Law No. 1 of 1974 concerning Marriage. One of the conditions in the Marriage Law regulates the lowest age limit for marriage. But in addition to being regulated regarding the lowest age limit for marriage, it is also regulated about the possibility of deviation from the lowest age limit in marriage through dispensation granted by the court. The formulation of the problem taken in this writing is (1) What is the procedure for applying for marriage dispensation in the Bawean Religious Court after the enactment of Law No. 1 of 1974 concerning Marriage?; and (2) What is the basis for the Judge's Consideration in giving a verdict or determination of the maturation of the bride-to-be in the Bawean Religious Court? . The research method uses a normative juridical approach , namely by reviewing Law No. 1 of 1974 concerning Marriage and Judge No. 6/Pdt.P/2017/PA. Bwn is related to the maturation of people. The results found are (1) The procedure for applying for marriage dispensation in the Religious Court is submitted by the parents of both men and women to the Religious Court that occupies the territory of residence, the Religious Court after examining in the trial and believing that there are things that make it possible to grant the Dispensation, then the Religious Court grants marriage dispensation with a determination; (2) The basis for consideration of granting maturation to prospective women in the Bawean Court is the concern of parents who see their child's relationship too close to their partner when they are not yet bound by a legal marriage will cause adverse effects if allowed to continue, such as adultery, extramarital pregnancy, marriage under hand. Keywords: Judge Considerations, Maturity, Marriage.